A Mathematical Model of Intermittent Gas Lift in Elevation-Production Operation with Line-Pack and Line-Drafting Phenomena in a Gas Line - Silvya Dewi Rahmawati; Tasmi Tasmi; Pudjo Sukarno; Agus Yodi Gunawan; Edy Soewono; Septoratno Siregar; Edward L. Tobing (Journal of Earth Energy Engineering, 2020)
This paper discusses a transient model of the intermittent gas lift technique in an oil well. The model is developed in the gas line, in the tubing-casing annulus, and the tubing. The line-pack and line-drafting phenomena in the gas line are considered in the model. A numerical approach will be used to solve the mathematical model that represents fluid flow during intermittent gas lift injection. The dynamics of important variables in the intermittent gas lift are investigated and analyzed to determine the best production strategy for intermittent gas lift. The variables are film thickness and velocity, slug height and velocity, and gas height and velocity. The relationships between surface injection control parameters (gas injection pressure and gas injection rate) and the velocity and height of film, gas, and liquid are shown in one cycle of the gas lift intermittent process. The higher the gas injection pressure, the faster the gas injection velocity, and the thinner the film thickness in the tubing. In order to obtain clean tubing from film thickness, the gas injection pressure needs to be optimized, which will lead to maintaining compressor discharge pressure availability. Detailed observation of the dynamic performance inside the tubing production well will give the optimum oil production rate for oil wells under a gas lift intermittent production strategy for field application.